Laterality Defects of the Heart: A Review of the Anatomical and Cardiological Approaches (Bangladesh Journal of Anatomy, 2018)
Heart is of mesodermal origin which undergoes a complex process of development. A number of congenital anomalies were encountered at the time of its development. Very little is known about the embryological background of these anomalies. We only encountered the congenital anomalies that was occurred at the time of establishment of the left-right axis of the embryo. This review includes causes, clinical presentations, diagnostic approaches, existing treatment and preventive measures if any persist for the followings: Dextrocardia, isomerism, transposition of great arteries or other forms of heterotaxy.Bangladesh Journal of Anatomy July 2018, Vol. 16, No. 2, pp. 51-55